Bilingual Resources, Vol. 1, No. 1, Fall 1977 - California State Univ., Los Angeles. National Dissemination and Assessment Center; California State Univ., Los Angeles. National Dissemination and Assessment Center ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1977)
This journal, the first in a new series of publications, consists of guides to instructional materials and articles on subjects of interest to teachers in bilingual education programs. The following articles and regular features appear in this issue: (1) Publications of the National Dissemination and Assessment Center, Los Angeles, a list of selected bilingual curricular and testing materials; (2) Instructional and Resource Materials: Annotations; (3) "Reading and the Bilingual Child," by Doris Ching, an excerpt; (4) The Misinterpretation of Grade Equivalents; (5) Selected Principles on Culture-Fairness in Testing; (6) Test Review: SWRL Proficiency Verification Systems in Mathematics; (7) A Feature Review, Chinese Cultural Heritage in America: Children's Readers of Festivals, includes brief descriptions of the individual booklets in the series; and (8) National Network Highlights, discussing the Asian American Bilingual Center, Berkeley. (AMH)
Availability: National Dissemination and Assessment Center, 5151 State University Drive, King Hall C2094A, Los Angeles, California, 90032 ($2.50 per copy, $6.00 Subscription of 3).
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
ERIC Note: Parts may not reproduce clearly.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Biculturalism; Bilingual Education; Book Reviews; Chinese Americans; Chinese Culture; Culture Fair Tests; Elementary Secondary Education; English (Second Language); Grade Equivalent Scores; Guides; Information Sources; Instructional Materials; Language Instruction; Mathematics Materials; Publications; Reading Instruction; Resource Materials; Second Language Learning; Teaching Methods; Testing; Elementary Secondary Education Act Title VII; Journal Articles